Pengaruh Pemeliharaan Drainase dan Kebersihan Lingkungan terhadap Fungsi Saluran Air di Perumahan Bumi Koperasi, RT 22, Sukodono, Sidoarjo - Intan Widyawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Drainage problems in residential areas, particularly in Bumi Koperasi Housing, RT 22, Sukodono, Sidoarjo, have led to pooling and flooding risks due to blockages and sedimentation. This community service research aims to analyze the impact of drainage maintenance and environmental cleanliness on the function of water channels. The method used was descriptive-participatory with the ABCD (Asset-Based Community Development) approach, including identifying critical points, cleaning channels, evaluating flow capacity using dimension and water discharge measurements, observation, photo documentation, and resident interviews. The results of the community service program showed that routine maintenance and sediment removal successfully increased flow capacity by up to 60% and reduced pooling in three critical locations by up to 70%. Furthermore, active community participation increased significantly, with more residents involved in community service and understanding the importance of maintaining clean channels. These findings confirm that physical interventions combined with strengthening community social capital can improve drainage performance, reduce flood risk, and enhance the quality of residential environments.